2012
DOI: 10.1007/s00726-012-1278-y
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocopherol inhibits human prostate cancer cell proliferation by up-regulation of transglutaminase 2 and down-regulation of cyclins

Abstract: To establish a system to study differentiation therapy drugs, we used the androgen-independent human prostate PC-3 tumor cell line as a target and α- and γ-tocopherol as inducers. Effects of α- and γ-tocopherol on the cell cycle, proliferation and differentiation, were examined. A more significant growth inhibition activity for γ- than for α-tocopherol was observed. Flow cytometry analysis of α- and γ-tocopherol-treated prostate carcinoma PC3 cells showed decreased progression into the S-phase. This effect, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…γ-tocopherol exhibited greater potency including increased expression and activity of transglutaminase 2 , a cell differentiation marker that induces differentiation and eventual apoptosis. Given that γ-tocopherol is more readily metabolized into γ-carboxyethyl hydroxychroman and previous studies with tocopherol metabolites have shown similar results, it is possible that γ-tocopherol metabolites may be the effector agent resulting in growth inhibition of PC-3 cells, although other studies suggest metabolite formation is largely a detoxification mechanism with little or no effect on proliferation [6669]. Tocotrienols were consistently more potent at inhibiting cell growth and inducing apoptosis in mouse mammary epithelial cells, CL-S1 when compared to tocopherols [70].…”
Section: Tocopherol and Tocotrienolmentioning
confidence: 93%
See 3 more Smart Citations
“…γ-tocopherol exhibited greater potency including increased expression and activity of transglutaminase 2 , a cell differentiation marker that induces differentiation and eventual apoptosis. Given that γ-tocopherol is more readily metabolized into γ-carboxyethyl hydroxychroman and previous studies with tocopherol metabolites have shown similar results, it is possible that γ-tocopherol metabolites may be the effector agent resulting in growth inhibition of PC-3 cells, although other studies suggest metabolite formation is largely a detoxification mechanism with little or no effect on proliferation [6669]. Tocotrienols were consistently more potent at inhibiting cell growth and inducing apoptosis in mouse mammary epithelial cells, CL-S1 when compared to tocopherols [70].…”
Section: Tocopherol and Tocotrienolmentioning
confidence: 93%
“…It is important not to disregard other members of the vitamin E family as well since there are studies indicating γ-tocopherol, the second most common vitamin E isoform could be a beneficial micronutrient. Further, vitamin E transport proteins could prove to be key factors in determining the efficacious property of vitamin E [6667]. …”
Section: Vitamin E and Cancer Prevention Studies: A Short Summary mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar finding was observed in the ATBC study (35). γ-Tocopherol has been shown to promote apoptosis (36) and inhibit growth (37) in prostate cancer cell lines. Similarly with vitamin E, studies on β-carotene have reported inverse (3840) or positive (29) associations, and null associations with β-carotene or other carotenoids (41–46).…”
Section: Discussionmentioning
confidence: 99%